Design method of flexural capacity of BFRP bar reinforced ecological high ductility cementitious composites beam. (March 2022) - Chai, Li-Juan; Guo, Li-Ping; Chen, Bo; Li, Zhu; Zheng, Zhi
Abstract: Steel expansion joints are damaged under traffic loading, and bridge deck link slab made by basalt fiber reinforced polymer (BFRP) bar reinforced ecological high ductility cementitious composites (Eco-HDCC) can be used to replace the expansion joints. To provide the structural design guideline of bridge deck link slab, experimental study and theoretical analysis of BFRP bar reinforced Eco-HDCC bending beam were conducted. The diameter of BFRP bar and cover thickness were considered. Monotonic and cyclic loading modes were compared. When the diameter is within 8 mm ∼ 16 mm and the cover thickness is within 25 mm ∼ 35 mm, the peak load of beam increases as the diameter increases or the cover thickness decreases. Monotonic and cyclic loading regimes have little effects on the peak load. Before the beam cracks, diameter and cover thickness have little effects on the strain of BFRP bar and compressive strain of Eco-HDCC. After the beam cracks and under the same load, both the strain of BFRP bar and compressive strain of Eco-HDCC decrease as the diameter increases. Loading regime has little effect on the envelope curves of load-BFRP bar strain and load-Eco-HDCC compressive strain. Calculation formulas of flexural capacity for under-reinforced beam, balanced-reinforced beam and over-reinforced beam are established as the tensile stress–strain relationship of Eco-HDCC is involved. Compared with the test results, the calculation formulas of flexural capacity are feasible.